2016
DOI: 10.1377/hlthaff.2016.0017
|View full text |Cite
|
Sign up to set email alerts
|

Gun Violence, Mental Illness, And Laws That Prohibit Gun Possession: Evidence From Two Florida Counties

Abstract: Gun violence kills about ninety people every day in the United States, a toll measured in wasted and ruined lives and with an annual economic price tag exceeding $200 billion. Some policy makers suggest that reforming mental health care systems and improving point-of-purchase background checks to keep guns from mentally disturbed people will address the problem. Epidemiological research shows that serious mental illness contributes little to the risk of interpersonal violence but is a strong factor in suicide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…From a European perspective, mass shootings in America might be almost eliminated by modest gun controls. In the United States, nuanced discussion about how psychiatry might even contribute positively to the debate is well advanced (Metzl & MacLeish, ; Swanson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…From a European perspective, mass shootings in America might be almost eliminated by modest gun controls. In the United States, nuanced discussion about how psychiatry might even contribute positively to the debate is well advanced (Metzl & MacLeish, ; Swanson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Swanson et al 2016) used public records over an 8-year period to examine gun disqualifications and arrests for violent gun crimes as well as firearm suicides for a sample of people receiving publicly funded treatment for severe mental illness. This study found that the implementation of an increased level of NICS reporting of involuntary commitment incidents (in 2007) led to a substantial reduction in the rate of arrest for violent crime for individuals who had, in fact, been involuntarily committed.…”
Section: Current Policy Initiatives Addressing Gun Violence and Mementioning
confidence: 99%
“…Being denied a gun purchase based on the history of involuntary commitment alone, however, only accounted for 13% of the disqualifications of those who had a prior involuntary commitment and were arrested for a violent crime; 52% of these individuals were disqualified by virtue of a prior criminal record issue. Thus, the narrow criteria of involuntary commitment as an excluding factor affected a relatively small proportion of the patients who went on to engage in significant violence; past history of criminality would have disqualified these individuals (Swanson et al 2016). …”
Section: Current Policy Initiatives Addressing Gun Violence and Mementioning
confidence: 99%
See 1 more Smart Citation
“…Further, even if all of these potential public mass murderers were subjected to a mental health background check, they would all have to have had a serious mental illness, whereas we found evidence of any mental illness in only half of our sample. Finally, even if all of these potential public mass murderers did have a serious mental illness and were subjected to a mental health background check, they would all have to have been in the small minority of those with serious mental illness who acquire disqualifying mental health records (Swanson et al ). In short, existing research and our findings make it implausible that any significant number of potential public mass murderers have been prevented from obtaining firearms by federal mental health background checks.…”
Section: Discussionmentioning
confidence: 99%